Dampak Kesehatan Anak Pada Periode Embrio, Janin, Bayi dan Usia Sekolah dengan Ayah Perokok - Fitra - Duhita; Novi Indah Rahmawati (Jurnal Kesehatan Vokasional, 2019)
Background: Almost 60,3% of smoker in Indonesia are men, and only 1% in women. That is caused by smoking for a women as a taboo. But smoking for a men as a symbol of masculineism, manner in social interaction with their community and best choice to ignoring negative feeling. If smoking habit in men continuing until they become a father, its bring negative effect for their children. Objective: This study aim to know kind of effect to his children while father as a smokerMethods: This is literatur review from research article which discuss about the effect of cigarete smoke also father as smoker to children while in conception periode, future health and development.Result: The review showed that exposure of the smoke in embrionic periode can cause spontaneouse abortion; in foetal periode cause preterm delivery and low birth weight baby; in infant periode increase risk of asthma and mental development delay.  All of that condition is caused by chemical compounds of the smoke. In other hand, children who have father whose smoking are risk three times greater to be smoker too in the future. Furthermore, it cause the chain of smoker will difficult to cut and bring negative impact for next generation. Conclusion: From this review’s result, its important  for primary health care provider to promote health education for every father in the family to wise while smoking.